Alternative Threat Methodology - Charles B. King III (Journal of Strategic Security, 2011)
Of the many challenges facing risk analysis practitioners, perhaps the most difficult to overcome is in the field of terrorist threat analysis. When estimating the threat associated with naturally occurring events, historical data provides a great deal of insight into the frequency of those events. Threat associated with accidents applies many operations research tools to gauge future failure-rates (Failure Mode and Effects Analysis being perhaps the most widely known). However, estimating the probability of an individual's or group's attacking a specific (or even a generic) target is an element of risk analysis in which art and intuition are applied far more regularly than is science.